THE EFFECTIVENESS OF PROGESTERONE HORMONE OR PGF2α AND hCG APPLICATION TO INCREASE REPRODUCTIVE EFFICIENCY OF POSTPARTUM OF ANESTRUS PE GOATS - Muhammad Syawal; Tuty L Yusuf; Muhammad Agil (Universitas Syiah Kuala, 2017)
This study aimed to improve reproductive condition of postpartum anestrus of Etawa crossbreed (PE) goats using PGF2α hormone or progesterone (controlled internal drug release/CIDR-G) and improve pregnancy success from artificial insemination (AI) with human chorionic gonadotrophin (hCG) hormone administration. Administration of progesterone increased estrus by 100%, which was higher than the 70% produced from prostaglandin F2 alfa (PGF2α) administration. Estrus onset in CIDR group (35.80±13.33 hours) was faster than PGF2α group (45.6±9.2 hours). Clinical signs of vulva (redness and swollen) were more intense in CIDR-G group (80% and 70%, respectively) compared to PGF2α group (70% and 57%, respectively). Estrus duration in PGF2α group (52.17±3.34 hours) was longer than CIDR-G group (49.61±3.56 hours). Pregnancy success in group given hCG was 66.7% while in non-hCG group was 50%. In conclusion, CIDR-G and PGF2α administration is effective to induce estrus of postpartum anestrus PE goats. Administration of hCG at the onset of estrus is effective to improve pregnancy success.